2014
DOI: 10.1002/eat.22314
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning in two treatments for adolescent anorexia nervosa

Abstract: Objective Family functioning impairment is widely reported in the eating disorders literature, yet few studies have examined the role of family functioning in treatment for adolescent anorexia nervosa (AN). This study examined family functioning in two treatments for adolescent AN from multiple family members’ perspectives. Method Participants were 121 adolescents with AN ages 12–18 from a randomized-controlled trial comparing family-based treatment (FBT) to individual adolescent-focused therapy (AFT). Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 44 publications
9
63
1
3
Order By: Relevance
“…These latter patients in fact showed less conflictual dyadic interactions with parents, although triadic interactions were the most deficient and problematic. Reinstate a physiological adolescent development trajectory would be in these cases more difficult but it can be considered a pivotal aim to be targeted in the recovery process, because severe anorexia and more marked psychiatric problems appeared to be closely linked (Ciao et al, ; Wallis, Miskovic‐Wheatley, et al, ). We believe that such a goal can be more easily achieved using both an individual approach to support the adolescent and a family or parental one, in order to help parents in accepting and enhancing the adolescent's changes as well as in tackling the eventual premorbid family and parental issues, which may have prevented those changes (Godart et al, ; Wallis, Miskovic‐Wheatley, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These latter patients in fact showed less conflictual dyadic interactions with parents, although triadic interactions were the most deficient and problematic. Reinstate a physiological adolescent development trajectory would be in these cases more difficult but it can be considered a pivotal aim to be targeted in the recovery process, because severe anorexia and more marked psychiatric problems appeared to be closely linked (Ciao et al, ; Wallis, Miskovic‐Wheatley, et al, ). We believe that such a goal can be more easily achieved using both an individual approach to support the adolescent and a family or parental one, in order to help parents in accepting and enhancing the adolescent's changes as well as in tackling the eventual premorbid family and parental issues, which may have prevented those changes (Godart et al, ; Wallis, Miskovic‐Wheatley, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also clear that self‐report questionnaires capture the family components' perceptions and viewpoints, which may largely differ from the observers' ratings of the family interactions (Balottin, Nacinovich, Bomba, & Mannarini, ). However, two (Ciao et al, ; Wallis, Miskovic‐Wheatley, et al, ) out of three studies (Ciao et al, ; Wallis, Rhodes, et al, ; Wallis, Miskovic‐Wheatley, et al, ) following the cited systematic review (Holtom‐Viesel & Allan, ) applied only self‐report measures, whereas one study applied an ad hoc qualitative interview (Wallis, Rhodes, et al, ). Moreover, few studies applied observer‐rated measures along with the self‐report ones, and demonstrated that the families of patients with anorexia perceived their functioning to be better than the observers' ratings (Gowers & North, ; Wallin & Hansson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Eisler et al, 2003;Le Grange and Eisler, 2008;Lock et al, 2006) Family functioning has been measured both as a unitary construct reflecting the general functioning of the family as a whole and as a set of several aspects, such as flexibility, cohesion, and communication. Existing evidence suggests that there is a substantial agreement within family members dealing with AN in perceiving an impairment of the general family functioning and a strong dissatisfaction with family life (Casper and Troiani, 2001;Ciao et al, 2015;Cook-Darzens et al, 2005;Emanuelli et al, 2004;McDermott et al, 2002;Szabo et al, 1999); on the other hand, when considering specific dimensions of family functioning, significant differences are found between girls with AN and their parents, even though research shows variable and sometimes conflicting results (Ciao et al, 2015;Holtom-Viesel and Allan, 2014).…”
Section: According To the Diagnostic And Statisticalmentioning
confidence: 99%
“…Qualitative research suggests that families are concerned about the impact of AN and FBT on siblings (Withers et al, ); however, there has been no quantitative study of sibling well‐being within an FBT programme. Of importance, there is evidence that family functioning actually improves during FBT (Ciao, Accurso, Fitzsimmons‐Craft, Lock, & Le Grange, ). Thus, an alternative possibility is that sibling well‐being could likewise improve during FBT.…”
mentioning
confidence: 99%